Cell dispersion during biofilm formation by Scedosporium apiospermum, Scedosporium aurantiacum, Scedosporium minutisporum and Lomentospora prolificans - Mello, Thaís P.; Barcellos, Iuri C.; Branquinha, Marta H.; Santos, André L.S. (Current research in microbial sciences, 2023)
•Cell dispersion occurs along the Scedosporium/Lomentospora biofilm development.•Mucin and abundance of nutrients are factors that induce the biofilm dispersion.•Different glucose concentrations do not interfere with cell dispersion.•Poor nutrient environment inhibits cell dispersion.•The antifungal voriconazole does not interfere with cell dispersion. Dispersion is an essential step in the lifecycle of biofilms, since it enables the dissemination of microbial cells and, consequently, the potential colonization of new sites. Filamentous fungi belonging to the Scedosporium/Lomentospora genera are opportunistic human pathogens able to form multidrug-resistant biofilms on surfaces of different chemical compositions, environments and nutritional conditions. Despite the rising understanding of how biofilms are formed by Scedosporium/Lomentospora species, the cell dispersal step has not yet been explored. In the present study, the cell dispersion was investigated during biofilm formation by S. apiospermum, S. minutisporum, S. aurantiacum and L. prolificans cells. The results revealed that conidia were the major type of dispersed cells, which were detected throughout biofilm development (from 24 to 72 h). Dispersion was not influenced by increased glucose concentration (the main source for energetic metabolism) neither the presence of voriconazole (the most common antifungal used to treat scedosporiosis); however, the presence of mucin (a component of mucous, present in the lungs of cystic fibrosis patients, who are usually affected by these filamentous fungi) triggered cell dispersion. Contrarily, a poor nutritional environment (e.g., phosphate-buffered saline) inhibited this step. Overall, our study reveals new insights into the biofilm development of Scedosporium/Lomentospora species. [Display omitted]